2018
DOI: 10.1002/ijch.201800058
|View full text |Cite
|
Sign up to set email alerts
|

Solid State and Aggregation Induced Emissive Chromophores by Multi‐component Syntheses

Abstract: The formation of chromophores by multi‐component reactions is a synthetically favorable and highly practical chromogenic concept for exploring functional and structural space of solid state and aggregation induced emission (AIE). The underlying reactivity is enabled by alkynoyl intermediates, which are generated in a catalytic fashion and, thereby, open very mild entries to many consecutive one‐pot formations of luminophores. This account summarizes the multi‐component synthetic concept and presents very recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 83 publications
(34 reference statements)
0
14
0
1
Order By: Relevance
“…In recent years we could demonstrate that also quite polar heterocyclic systems, such as indolone merocyanines and quinoxalines motifs, can be AIE active . We therefore became interested in molecules with pronounced charge‐transfer (CT) character, which could finally provide access to blue emissive AIE chromophores.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years we could demonstrate that also quite polar heterocyclic systems, such as indolone merocyanines and quinoxalines motifs, can be AIE active . We therefore became interested in molecules with pronounced charge‐transfer (CT) character, which could finally provide access to blue emissive AIE chromophores.…”
Section: Methodsmentioning
confidence: 99%
“…Ein häufig verwendetes Strukturmotiv ist das Tetraphenylethen (TPE) und daraus abgeleitete Derivate, wie auch Anthracen‐ und Carbazol‐basierte Strukturen . In den letzten Jahren konnten wir zeigen, dass auch polare heterocyclische Systeme wie Quinoxaline oder Indolon‐Merocyanine AIE‐aktiv sein können …”
Section: Methodsunclassified
“…As part of our program to methodologically develop concise syntheses of functional chromophores by multicomponent reactions (MCR) (Levi and Müller, 2016a), we are particularly interested in MCR syntheses of fluorophores (Levi and Müller, 2016b; Riva et al, 2016; Merkt and Müller, 2018; Müller, 2018) and donor-acceptor systems that interact in the excited state via photo-induced electron transfer (PIET) (Kavarnos, 1993; Lemmetyinen et al, 2011; Wenger, 2011; Ricks et al, 2012; Vauthey, 2012), as shown by non-radiative fluorescence quenching (Bucci and Müller, 2006; Bay et al, 2013, 2014; Bay and Müller, 2014). This can be considered as chromophore-chromophore interactions at short distances, that is, between Dexter and Förster radii.…”
Section: Introductionmentioning
confidence: 99%